In vivo Delivery Tools for Clustered Regularly Interspaced Short Palindromic Repeat/Associated Protein 9-Mediated Inhibition of Hepatitis B Virus Infection: An Update - Kayesh, Mohammad Enamul Hoque; Hashem, Md Abul; Kohara, Michinori; Tsukiyama-Kohara, Kyoko (Frontiers in Microbiology, 2022)
Chronic hepatitis B virus (HBV) infection remains a major global health problem despite the availability of an effective prophylactic HBV vaccine. Current antiviral therapies are unable to fully cure chronic hepatitis B (CHB) because of the persistent nature of covalently closed circular DNA (cccDNA), a replicative template for HBV, which necessitates the development of alternative therapeutic approaches. The CRISPR/Cas system, a newly emerging genome editing tool, holds great promise for genome editing and gene therapy. Several in vitro and/or in vivo studies have demonstrated the effectiveness of HBV-specific CRISPR/Cas9 systems in cleaving HBV DNA and cccDNA. Although recent advances in CRISPR/Cas technology enhance its prospects for clinical application against HBV infection, in vivo delivery of the CRISPR/Cas9 system at targets sites remains a major challenge that needs to be resolved before its clinical application in gene therapy for CHB. In the present review, we discuss CRISPR/Cas9 delivery tools for targeting HBV infection, with a focus on the development of adeno-associated virus vectors and lipid nanoparticle (LNP)-based CRISPR/Cas ribonucleoprotein (RNP) delivery to treat CHB. In addition, we discuss the importance of delivery tools in the enhancement of the antiviral efficacy of CRISPR/Cas9 against HBV infection.